Green Synthesis, Characterization And Antimicrobial Evaluation Of Schiff Base Derivatives Derived From Aromatic Aldehydes And Amines - Maruti More, Swapnil; Taware, Shubhangi Vikrant; Shivani, Shivani; Sharma, Sachin; Sharma, Swati (Journal of Neonatal Surgery, 2025)
The present study reports the green synthesis of Schiff base derivatives obtained by condensing aromatic aldehydes with primary aromatic amines using eco-friendly reaction conditions. Schiff bases are widely recognized for their structural versatility and biological significance, particularly in antimicrobial therapy. In this work, green synthetic approaches such as solvent-free grinding and aqueous ethanol reflux were employed to avoid hazardous solvents and reduce environmental impact. The synthesized derivatives were characterized by physicochemical parameters, UV-Visible spectroscopy, FT-IR, and NMR techniques to confirm the imine (-C=N-) linkage formation. The compounds were further evaluated for their antimicrobial activity against Gram-positive (Staphylococcus aureus, Bacillus subtilis) and Gram-negative (Escherichia coli, Pseudomonas aeruginosa) bacterial strains as well as fungal species (Candida albicans, Aspergillus niger) using the agar well diffusion method. Several Schiff base derivatives demonstrated significant antimicrobial potential, suggesting their possible use as lead molecules for developing new antimicrobial agents.